Revisiting the Financial Year in India - Mohanty, Asit Ranjan; Mohanty, Avipsa (Archives of Business Research, 2016)
The Ministry of Finance, Government of India, has recently constituted an expert committee to look into the feasibility of changing the Financial Year in India. This has rekindled the debate which is now a hundred and fifty years old. A Financial Year is a period of 12 months used for estimating and analyzing the government’s financial accounts. The present financial year in India runs from the 1st April to the 31st March of the following year. It was adopted in 1867 on the grounds of aligning it with the British practice. The Financial Year has been subject to debate for so long considering the fact that it was adopted without taking into consideration local/ Indian customs. The current debate necessitates a re-evaluation of the Financial Year in India. This study has attempted to analyze the issue of changing financial year in India considering the international practices. After evaluating the current dynamics of India, this study suggests for a status quo. Keywords: Financial Year, Budget, Monsoon, India.